2022
DOI: 10.1108/ijccsm-02-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on agricultural productivity: a combination of spatial Durbin model and entropy approaches

Abstract: Purpose Global climate change characterized by an increase in temperature has become the focus of attention all over the world. China is a sensitive and significant area of global climate change. This paper specifically aims to examine the association between agricultural productivity and the climate change by using China’s provincial agricultural input–output data from 2000 to 2019 and the climatic data of the ground meteorological stations. Design/methodology/approach The authors used the three-stage spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…This decline might be due to change in climate and associated reduction in certain agricultural activities. For instance, Bai et al 64 observed the loss in agricultural production due to climate change in the TP for the period 2000–2019; consistent with our analysis.…”
Section: Resultssupporting
confidence: 92%
“…This decline might be due to change in climate and associated reduction in certain agricultural activities. For instance, Bai et al 64 observed the loss in agricultural production due to climate change in the TP for the period 2000–2019; consistent with our analysis.…”
Section: Resultssupporting
confidence: 92%
“…Agriculture has always been the backbone of Sri Lanka's rural population and paddy cultivation is the most common type of agriculture practiced by about 1.8 million farming families across the island. However, climate change has significant impacts on agriculture [1,2]. In the field of climate sciences, rainfall and temperature are the important variables which have great influence on crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is the end of a series of stages that cause rain to fall [21]. Bai et al [22], Joshi et al [23], Gornall et al [24], and Mechiche-Alami and Abdi [25] observe the dynamics of climate change on agricultural productivity. Climate change in China is having a negative and significant effect on agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%